A Study about Pork Farm in Surakarta as Export Commodity - Naufal Rhyo Ichwanda; Wilyam Lie; Septyanto Galan Prakoso (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2019)
Pork as one of most consumed meat in the world had a big potential to be on prospective international trade commodities. Asia, especially East Asia and Southeast Asia had a deep root culture of pork culinary even in Moslem-majority countries like Indonesia and Malaysia. Although its commodity price is considered low in the international trade, the demand of pork is relatively stable. Current top exporter of pork is being held by European Union, followed by United States and Canada, while the current top importer of pork is held by China followed by United States. Southeast Asia actually had a potential to develop its pork export and take some of international market but in reality Southeast Asian countries still struggling to develop their pork export. Between Southeast Asia countries only Thailand and Vietnam who are able to export their pork meat to other countries in a large scale. Therefore, we want to share the result of our qualitative study regarding this topic to enhance the knowledge about the condition and the prospect of this commodity and what barrier that hinder Southeast Asian countries from developing their pork market by using competitive advantage theory and pork farm in Surakarta, Indonesia as the study case. The results of our study are expected could be used as reference to develop pork export in Southeast Asia.